Effects of Climate Change on Korea’s Fisheries Production: An ARDL Approach - Hoonseok Cho; Pilgyu Jung; Mingyeong Jeong (Fishes, 2025)
This study investigates the impact of rising sea surface temperature (SST), increasing carbon dioxide (CO2) emissions, and precipitation variability (PREC) on Korea’s coastal and offshore fisheries production (COFP) from 1993 to 2023 using an autoregressive distributed lag (ARDL) model. The results confirm a long-run cointegration relationship, where a 1% increase in SST, CO2, and PREC is associated with respective declines of 3.52%, 0.82%, and 0.34% in COFP, respectively, suggesting persistent negative effects of ocean warming, acidification, and hydrological variability on fisheries production. Robustness checks using Fully Modified Ordinary Least Squares (FMOLS) and Canonical Cointegrating Regression (CCR) validate the stability of the ARDL results. The short-run analysis reveals that past production levels significantly influence current COFP, while SST fluctuations exhibit delayed but economically meaningful effects. The error correction term (−0.75, p < 0.01) confirms a rapid adjustment toward equilibrium following short-term deviations. These findings underscore the necessity of climate-resilient fisheries management. Policy recommendations include adaptive harvest regulations, climate-integrated stock assessments, and enhanced international cooperation for transboundary fish stocks. Additionally, expanding Marine Protected Areas, promoting climate-resilient aquaculture, and strengthening stock enhancement programs through selective breeding and seed release of climate-adapted species are essential for sustaining fisheries under climate change.